Analysis of the Influence of Location, Service Quality, and Price Perception on Purchasing Decisions at Yuki Store Rantau Prapat - Daulay, Jelita Hati; Siregar, Nurintan Asyiah; Pitriyani, Pitriyani (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to examine the influence of location, service quality, and price perception on purchasing decisions at Yuki Store in Rantau Prapat, North Sumatra. The research employs a quantitative descriptive approach. The population consists of customers who have made purchases at Yuki Store in Rantau Prapat, with a sample size of 96 respondents. Data analysis was conducted using SmartPLS 4 application. The results indicate that location has a t-statistic value of 1.273, service quality has a t-statistic of 1.990, and price perception has a t-statistic of 2.120. Although the location does not have a significant effect on purchasing decisions, service quality and price perception significantly influence purchasing decisions. The p-value for location is 0.203 (> 0.05), and for service quality and price perception, it is less than 0.05, demonstrating that service quality and price perception have significant positive effects on purchase decisions. The study provides valuable insights for the management of Yuki Store to focus on improving service quality and price perception to enhance consumer purchasing decisions.